PENGARUH PEMAHAMAN AKUNTANSI DAN PENERAPAN SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN PADA USAHA MIKRO KECIL DAN MENENGAH (USAHA KULINER KECAMATAN PASAR MINGGU JAKARTA SELATAN) - Astuti, Resi Puji; Jamain, Tries Handriman (Jurnal Kewirausahaan Bukit Pengharapan, 2024)
This research aims to examine the influence of understanding accounting and the application of accounting information systems on the quality of financial reports in Culinary Business UMKM, Pasar Minggu District, South Jakarta. The research object is culinary business actors (UMKM, Pasar Minggu District, South Jakarta). The population was 5,387, using purposive sampling techniques. The data analysis technique uses a Likert scale. The research results show that understanding accounting and implementing information systems partially and simultaneously influence the quality of financial reports.